KEEFEKTIFAN METODE ACTIVE LEARNING DALAM PEMBELAJARAN KANJI N4 (PENELITIAN EKSPERIMEN PADA MAHASISWA TINGKAT II TAHUN AJARAN 2018/2019 PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU) - Lailasari Lailasari; Hermandra Hermandra; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research discusses about the effectiveness of active learning methods In N4 Kanji characters learning of Japanese Language Education Level II Students Faculty of Teacher Training and Education Riau University, 2018.The purpose of this research was to determine the effectiveness of the active learning method. The object of this research is level II Japanese Language Education StudentsFaculty of Teacher Training and Education, Riau University. This research is quasi-experimental, which is carried out by the comparison class and used Pretest-Posttest Control Group Design. Data collection techniques are carried out using test questions and questionnaires.. The average pretest value obtained by the control class was 65,83 and the posttest value of the control class was 66,33. There was a significant effect on the active learning method of N4 Kanji characters learning as evidenced in the SPSS Independent Sample t-test output, obtained Sig (2-tailed) value of 0.012 < 0.05, accordingly to the basis of decision-making in the Independent sample t-test, then it was concluded that alternative hypothesis (Ha) was accepted and Null hypothesis (Ho) was rejected, which means that there were significant differences between the values of the experimental and control classes. It can be seen that the experimental class has a higher average than the control class. And can be concluded the active learning method increase the ability of N4 Kanji characters learning for the Japanese Language students of Riau University in 2018.Key Words: Effectiveness, Active Learning, Kanji N4